Politik Pengakuan Perempuan Dengan Disabilitas Pasca Bencana Gempa Di Yogyakarta - Fina Itriyati; Deshinta Dwi Asriani (Departemen Sosiologi Universitas Gadjah Mada, 2012)
This study is a preliminary study of the politics of recognition of women with disabilities in th eaftermath of the 2006 earthquake in Bantul and Klaten, Yogyakarta and Central Java. In this preliminary study, it is found that there is transformation in the disability movement in both regions. The author would like to underline that the role of new women with disabilities affected by earthquake can encourage the transformation of the women with disabilities’ movement. These changes can be seen from all sides which before the earthquake, the discourse of women with disabilities are seen as a personal tragedy wher edisability issues are seen as an individual problem. The common approach used to deal with them is a charity activities, training services that are clinically aimed to make them as normal people and have independent lives. After the earthquake, there are a lot of DPO(Disabled People Organization) and association sfor persons with disabilities which accomodate not just those affected by the earthquake, but also all persons with disabilities who had been hidden by their families and socially marginalized. They appear to becoming out and giving a lesson to the people that the differences are common and normalization project is a choice that they have rights to refuse if it is not desired by them. In fact, they also have been able to counter the mainstream women’s movement discourse that their interests are also entitled to be accommodated in universal women’s discourse. This preliminary study which conducted by qualitative research methods withan ethnographic approach is still very early and still continuing with further research.Key words: women with disabilities, earthquake, politics of recognition, DPO (Disabled People Organization), individual and social model of disabilities